Durability of conrete using fly ash as a partial replacement of cement - Nath, Pradip (Curtin University, 2010)
Utilization of fly ash as a supplementary cementitious material adds sustainability to concrete by reducing the green house gas emission associated with cement production. Fly ash is a by-product of coal fired power stations. The properties of fly ash depend on the type of coal and its burning process. Due to the variation in composition, different fly ash affects the properties of concrete differently. Research data on the performance of concrete containing the Western Australian fly ash is scarce in literature. In this study, mechanical and durability properties of high strength concrete using Class F fly ash from Western Australia were investigated. The ACI 211.4R-08 guidelines were followed to design two series of concretes, each having one control concrete and two fly ash concretes using 30% and 40% fly ash as cement replacement. Fly ash concretes of series A were designed by adjusting the water to binder (w/b) ratio and total binder content to achieve the same strength grade of control concrete. In series B, w/b ratio and total binder content were kept constant in all the three mixtures. Samples were water cured for 7 and 28 days; and were tested at different ages. The mechanical properties were tested by compressive strength, tensile strength and flexural strength test. The investigated durability properties were drying shrinkage, volume of permeable voids, water and air permeability, carbonation and chloride ion penetrability.The 28-day compressive strength of the concrete mixtures varied from 65 to 85 MPa. The fly ash concretes showed lower drying shrinkage than control concrete when designed with adjusted w/b ratio and the total binder content. Inclusion of fly ash reduced sorptivity and water permeability significantly at 28 days. Fly ash showed no adverse affect on air permeability of concrete. Fly ash concretes showed similar carbonation and had less chloride ion penetration as compared to the similar grade control concrete. In general, incorporation of fly ash as partial replacement of cement improved the durability properties of concrete at early age when w/b ratio was adjusted to achieve similar 28-day strength of the control concrete. The durability properties improved with the increase of fly ash content from 30% to 40% of the binder and with the increase of age. Fly ash concretes of series A achieved similar service life of control concrete in carbonation and resulted in higher service life than that of the control concrete, when chloride diffusion was considered as the dominant form of attack.